Ensuring people's welfare in later life: lessons from Italy in pandemic times - Lamura, Giovanni (Magyar Gerontológia, 2020)
INRCA IRCCS (National Institute of Health and Science on Ageing), Centre for Socio-Economic Research on Ageing, ItalyKey words: residential care, home-based care, migrant carers, COVID-19     In this presentation, the impact of the COVID-19 pandemic on the Italian long-term care system will be illustrated, taking specifically into consideration two of its main pillars: residential care and home-based care.To this purpose, in the introduction the main features of the Italian system will be presented in detail. They include the overwhelming role of cash benefits over the rather marginal presence of in-kind services, and the use of such cash benefits by households to employ, on a private – and often undeclared – basis, care workers, who very often have a migrant background.  Following the introductory section, the impact of the pandemic on the Italian system will be analysed, in terms of hospitalisations, casualties and other effects on both residential and home-based care sectors. This will include an overview of the main challenges experienced by both care recipients and providers, as well as of the main measures adopted by public authorities to address them.Finally, the contribution will conclude by highlighting the main lessons emerging from the Italian experience, and identifying the main recommendations for the future.